Immunoreactivity of a Putative ECF σ Factor, LIC_10559, from Leptospira interrogans with Sera from Leptospira-Infected Animals - Sabina Kędzierska-Mieszkowska; Zbigniew Arent (Pathogens, 2023)
L. interrogans belongs to highly invasive spirochaetes causing leptospirosis in mammals, including humans. During infection, this pathogen is exposed to various stressors, and therefore, it must reprogram its gene expression to survive in the host and establish infection in a short duration of time. Host adaptation is possible thanks to molecular responses where appropriate regulators and signal transduction systems participate. Among the bacterial regulators, there are σ factors, including ECF (extracytoplasmic function) σ factors. The L. interrogans genome encodes 11 putative ECF σE-type factors. Currently, none of them has been characterized biochemically, and their functions are still unknown. One of them, LIC_10559, is the most likely to be active during infection because it is only found in the highly pathogenic Leptospira. The aim of this study was to achieve LIC_10559 overexpression to answer the question whether it may be a target of the humoral immune response during leptospiral infections. The immunoreactivity of the recombinant LIC_10559 was evaluated by SDS-PAGE, ECL Western blotting and ELISA assay using sera collected from Leptospira-infected animals and uninfected healthy controls. We found that LIC_10559 was recognized by IgG antibodies from the sera of infected animals and is, therefore, able to induce the host’s immune response to pathogenic Leptospira. This result suggests the involvement of LIC_10559 in the pathogenesis of leptospirosis.